2018
DOI: 10.1210/js.2018-00007
|View full text |Cite
|
Sign up to set email alerts
|

Notch-1 Signaling Activation and Progesterone Receptor Expression in Ectopic Lesions of Women With Endometriosis

Abstract: ContextProgesterone (P) resistance is a hallmark of endometriosis, but the underlying mechanism(s) for loss of P sensitivity leading to lesion establishment remains poorly understood.ObjectiveTo evaluate the association between Notch-1 signaling activation and P resistance in the progression of endometriosis.DesignCase control study; archived formalin-fixed, paraffin-embedded tissues.SettingUniversity hospitals (United States, Taiwan).PatientsWomen with endometriosis; human endometrial stromal cell line (HESC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Previous studies on endometrial and endometriotic stroma cells employing the GSI DAPT had demonstrated reduced generation and nuclear localization of the intracellular domain of notch, respectively . The application of an unbiased screening approach has produced a second important outcome of our study, as it revealed an impact of GSI on stemness‐related genes other than notch.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Previous studies on endometrial and endometriotic stroma cells employing the GSI DAPT had demonstrated reduced generation and nuclear localization of the intracellular domain of notch, respectively . The application of an unbiased screening approach has produced a second important outcome of our study, as it revealed an impact of GSI on stemness‐related genes other than notch.…”
Section: Discussionmentioning
confidence: 74%
“…Although short‐term treatments resulted in moderate effects, our colony formation assays indicate that prolongation of the treatment substantially enhances treatment efficacy. A decrease in cell proliferation was recently also observed in an endometrial stroma cell line upon treatment with a different GSI, DAPT, indicating that γ‐secretase inhibition affects both the epithelial and stromal compartments of the endometrium . Decreased proliferation would be in line with a reduction in stem cell‐like properties, as stem cells exhibit an unlimited proliferative potential …”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations